Neuroprotective Activity of (-)-Epigallocatechin Gallate against Lipopolysaccharide-Mediated Cytotoxicity. (12th April 2016) - Liu, Jin-Biao; Zhou, Li; Wang, Yi-Zhong; Wang, Xu; Zhou, Yu; Ho, Wen-Zhe; Li, Jie-Liang
Abstract : Lipopolysaccharide- (LPS-) mediated systemic inflammation plays a critical role in neurodegenerative diseases. The present study was conducted to evaluate the protective effects of epigallocatechin gallate (EGCG), the major component in green tea, on LPS-mediated inflammation and neurotoxicity. LPS treatment of macrophages induced expression of proinflammatory cytokines (TNF- α, IL-1 β, and IL-6). However, EGCG pretreatment of macrophages significantly inhibited LPS-mediated induction of these cytokines. In addition, EGCG significantly diminished LPS-induced inflammatory cytokines in the peripheral mononuclear blood cells (PBMCs). Supernatant from EGCG-pretreated and LPS-activated macrophage cultures was found to be less cytotoxic to neurons than that from non-EGCG-pretreated and LPS-activated macrophage cultures. Furthermore, EGCG treatment of neurons could inhibit LPS-induced production of reactive oxygen species (ROS). Thus EGCG represents a potent and useful neuroprotective agent for inflammation-mediated neurological disorders.